Concerted Bimetallic Nanocluster Synthesis and Encapsulation via Induced Zeolite Framework Demetallation for Shape and Substrate Selective Heterogeneous Catalysis. Issue 22 (2nd May 2018) - Iida, Takayuki; Zanchet, Daniela; Ohara, Koji; Wakihara, Toru; Román‐Leshkov, Yuriy
Abstract: Bimetallic nanoparticle encapsulation in microporous zeolite crystals is a promising route for producing catalysts with unprecedented reaction selectivities. Herein, a novel synthetic approach was developed to produce PtZn x nanoclusters encapsulated inside zeolite micropores by introducing Pt 2+ cations into a zincosilicate framework via ion exchange, and subsequent controlled demetallation and alloying with framework Zn. The resulting zeolites featured nanoclusters with sizes of approximately 1 nm, having an interatomic structure corresponding to a PtZn x alloy as confirmed by pair distribution function (PDF) analysis. These materials featured simultaneous shape and substrate specificity demonstrated by the selective production of p ‐chloroaniline from the competitive hydrogenation of p ‐chloronitrobenzene and 1, 3‐dimethyl‐5‐nitrobenzene. Abstract : Encapsulated : A new method to produce PtZn x bimetallic nanoclusters encapsulated inside MFI zeolite crystals was developed by introducing Pt 2+ cations into a zincosilicate framework by ion exchange, and subsequent controlled demetallation and reduction. The resulting zeolites catalysts featuring PtZn x nanoclusters have both shape and substrate specificity.